The Relationship Between Attitudes Toward Inclusion, Beliefs About Teaching and Learning, and Subsequent Automatic Evaluations Amongst Student Teachers - Börnert-Ringleb, Moritz; Westphal, Andrea; Zaruba, Nicole; Gutmann, Franziska; Vock, Miriam (Frontiers in Education, 2020)
Teachers’ attitudes towards inclusion are frequently cited as being an important predictor of how successfully a given inclusive school system is implemented. At the same time, beliefs about the nature of teaching and learning are discussed as a possible predictor of attitudes towards inclusion. However, more recent research emphasizes the need of considering implicit processes, such as automatic evaluations, when describing attitudes and beliefs. Previous evidence on the association of attitudes towards inclusion and beliefs about teaching and learning is solely based on explicit reports. Therefore, this study aims to examine the relationship between attitudes towards inclusion, beliefs about teaching and learning, and the subsequent automatic evaluations of pre-service teachers (N = 197). The results revealed differences between pre-service teachers’ explicit attitudes/beliefs and their subsequent automatic evaluations. Differences in the relationship between attitudes towards inclusion and beliefs about teaching and learning occur when teachers focus either on explicit measures or automatic evaluations. These differences might be due to different facets of the same attitude object being represented. Relying solely on either explicit measures or automatic evaluations at the exclusion of the other might lead to erroneous assumptions about the relation of attitudes towards inclusion and beliefs about teaching and learning.